Effort of Investigation by Satreskrim to Improve the Disclosure of Theft Crimes in Brebes Police (Advances in Police Science Research Journal, 2024)
Theft has now become a complex problem that is currently faced by the world including the Indonesian nation. It has been the main task of the police as law enforcement cracks down firmly on suspected perpetrators of theft crimes. However, in the investigation activities, there are weaknesses that make it not optimal, which is found to be factors - both internal factors such as human resources, infrastructure, budget, supervision and external such as public behavior that hinders the investigation of theft crimes. The preparation of this thesis uses a qualitative approach with a type of field research. Then to discuss the problems of the investigation of theft crimes by Satreskrim Brebes researchers use SWOT theory, management and related concepts focus the problem in this thesis. The results of this study can be concluded that the implementation of the investigation of theft crimes in Brebes police has not been running optimally. This is indicated by the decrease in the number of disclosure of theft crimes in the last 2 (two) year with several factors that affect it, among others, human resources that are not qualified and adequate, infrastructure that does not meet the needs of investigations, budgets that are not in accordance with the needs in the field, and supervision that has not been maximizedwhere this will be an obstacle in the investigation of theft crimes in Brebes police in the future.
Keywords: Upaya, Penyelidikan, Satreskrim